2014
DOI: 10.1136/archdischild-2013-304488
|View full text |Cite
|
Sign up to set email alerts
|

Parental presence during cardiopulmonary resuscitation of children: the experience, opinions and moral positions of emergency teams in France

Abstract: A majority of EPs and nurses were reluctant to have parents present during child CPR. Their attitude involved medical paternalism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 47 publications
4
19
0
11
Order By: Relevance
“…Physicians and nurses in this study expressed paternalistic views; they wanted to protect families from the trauma of resuscitations. This finding confirmed the results of five studies conducted in France, the UK and Canada (Fallis et al., ; Walker, ; McClement et al., ; Jabre et al., ; Tripon et al., ). Jabre et al.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Physicians and nurses in this study expressed paternalistic views; they wanted to protect families from the trauma of resuscitations. This finding confirmed the results of five studies conducted in France, the UK and Canada (Fallis et al., ; Walker, ; McClement et al., ; Jabre et al., ; Tripon et al., ). Jabre et al.…”
Section: Discussionsupporting
confidence: 87%
“…Nurses described how they weighed family benefits against the risk of family trauma, with nurses generally favouring benefit over risk from trauma. The family benefits acknowledged by participants in this study were consistent with perceived family benefits reported in other research, including providing relational closure and better coping; seeing everything was done; bringing the patient comfort; providing and receiving information; and making decisions about continuing the resuscitation (Tripon et al., ; Giles et al., ).…”
Section: Discussionsupporting
confidence: 84%
“…19 To ensure a quality service that offers the option to family members to stay with the patient in emergency or not, an elaborate policy and continuing education is required with the emergency service professionals. 8,16,21,23,27 In this context, the development of an awareness program to promote family presence in emergency situations and recognizing the benefits that this practice provides to the child is highlighted. Thus, it is possible to promote attitudes, behaviors and values that promote the inclusion of the family in child care in different hospital settings, including emergency rooms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous research found that parental presence can occasionally cause increased stress for staff (Davies et al 2005, Dudley et al 2009). This stress level was increased when resuscitation was not successful (Duran et al 2007) while some staff reported concern over the psychological trauma for parents and the risk of parental interference (Tripon et al 2014). A further potential challenge to parental presence was identified by Lowry (2012) who reported that staff are often concerned that parents may consider their actions as errors resulting in legal action.…”
Section: Discussionmentioning
confidence: 99%